An Analysis on Students’ Perception of the Application of Journalist Questions in Teaching Writing - Saofi, Muhammad (VELES Voices of English Language Education Society, 2019)
This research aimed at knowing about the teaching learning process through journalist questions and students’ perception of the application of journalist questions. This research is qualitative research. The subject of this research was the students of X IPS SMA NW Pringgabaya which consisted of 23 students. In addition, observation, questionnaire, and semi structured interview were used for collecting data. The finding revealed that the students have a good perception toward the implementation of journalist questions in teaching writing in the class. In addition, based on the result of observation, questionnaire and interview, the application of journalist questions was applied appropriately and the students’ perception in teaching writing is good.”